Non-noxious skin stimulation activates the nucleus basalis of Meynert and promotes NGF secretion in the parietal cortex via nicotinic ACh receptors - Hotta, Harumi (Springer Japan, 2014)
The effects of non-noxious skin stimulation on nerve growth factor (NGF) secretion in the parietal cortex were examined in anesthetized rats. Innocuous skin stimulation was delivered to the left hindlimb with a soft-hair brush. Extracellular NGF in the right parietal cortex was collected by microdialysis methods using a protein-permeable probe and was measured using an enzyme-linked immune-sorbent assay. Brushing produced a significant increase in extracellular NGF levels. This NGF response was not observed in rats pretreated with a nicotinic ACh receptor (nAChR) antagonist mecamylamine. We further examined whether brushing could activate the basal forebrain nucleus (nucleus basalis of Meynert, NBM), which is the main source of cholinergic fibers in the cerebral cortex, by means of functional MRI. The blood oxygen level-dependent signal in the right NBM was significantly higher during brushing compared to baseline. The results suggest that non-noxious skin stimulation activates NBM and promotes NGF secretion in the parietal cortex via nAChRs.